Unconscious overtone manipulation and transmission in flute performance: insights into musical expression and perception - Hiraiwa, Kai; Miura, Masanobu (Frontiers in Psychology, 2025)
This study aims to elucidate the overtone structure of the flute, examine the impact of acoustic parameter alterations on timbre perception, and foster a shared vocabulary among players and listeners. Employing principal component analysis (PCA) and listening experiments, the investigation delves into the ways in which players subconsciously adjust timbre and the manner in which these adjustments are perceived by listeners. The analysis concentrated on overtone components up to the fifth overtone (5f0) utilizing flute long-tones. PCA revealed that the first principal component (PC1) predominantly captured variations in the overall strength of overtones, whereas PC2 and PC3 were indicative of a balance around specific overtones. Furthermore, the coordinates of PC1, PC2 and PC3 for sounds deliberately produced with varying timbres were found to diverge. This finding indicates that the flute's timbre is influenced by both the overall loudness and the balance of overtones, and that players modify the overtone structure for expressive purposes. A listening experiment involving 28 participants ascertained that listeners were capable of distinguishing between different timbres, revealing significant differences in the percentage of coincident judgment based on the player and the musical register. Notably, professional players were more adept at conveying the intended timbre to the listener, and the middle register was identified as having the greatest potential for expressive variation.